ChemInform Abstract: Straightforward and Highly Diastereoselective Synthesis of 2, 2‐Di‐Substituted Perhydrofuro[2, 3‐b]pyran (and furan) Derivatives Promoted by BiCl3. Issue 48 (26th November 2013) - Ma, Xiaofeng; Tang, Qin; Ke, Jun; Zhang, Jichao; Wang, Cong; Wang, Haibo; Li, Yuxue; Shao, Huawu
Abstract The cyclization of cyclopropanated sugars, such as (I), with olefins, e.g. (II) proceeds highly diastereoselective to afford the title compounds (III).